High ACT score is not sufficient to reduce the risk of asthma exacerbations in asthma with low lung function. (April 2019) - Kwon, Jae-Woo; Jung, Heewon; Kim, Sae-Hoon; Chang, Yoon-Seok; Cho, You Sook; Nahm, Dong-Ho; Jang, An-Soo; Park, Jung-Won; Yoon, Ho Joo; Cho, Sang-Heon; Cho, Young-Joo; Choi, Byoung Whui; et al.
Abstract: Background: Low forced expiratory volume in 1 s (FEV1 ) is a risk factor for asthma exacerbations (AEs). We aimed to determine if asthma control could reduce the future risk of AEs in patients with low FEV1 . This study was conducted to evaluate the future risks of AEs within six months according to Asthma Control Test™ (ACT) score and FEV1 . Methods: A total of 565 patients with asthma were enrolled from the COREA cohort. The ACT score, lung function test, and number of AEs were assessed at baseline, three-month follow-up, and six-month follow-up with conventional asthma treatments by asthma specialists in real clinical settings. Results: Female sex, low ACT score, low FEV1, low FVC, and AE history in the previous three months were related with increased AEs within six months. AEs during six-month follow-up occurred in 24% of patients with ACT <20 and FEV1 < 60% at baseline. Among patients with an ACT score ≥20, 3.4% of patients with an FEV1 < 2.16 L and 9.8% of patients with FEV1 ≥ 2.16 L had experienced AEs (P = 0.01), although no differences were observed in the presence of AEs within six months according tothe predicted FEV1 (FEV1  ≥ 60% vs. FEV1 < 60%, 5.66% vs. 8.51%, P = 0.65). Conclusion: Patient with low FEV1 seemed to show higher risk of AEs than those with near-normal FEV1 despite ACT score ≥20 and asthma treatments. Therefore, treatment strategies that prevent AEs are needed in high-risk asthmatic patients. Highlights: Maintaining Asthma Control Test™(ACT) ≥ 20 could reduce the risk of asthma exacerbation in asthmatic patients with low FEV1. The risk seems still higher in those patients than asthmatics with near-normal FEV1 despite asthma treatments by specialists. Additional treatment strategies to prevent AEs seem to be needed for patients with low FEV1.